Origin and transport properties of two‐dimensional electron gas at ZnMgO/ZnO interface grown by MOVPE. Issue 10 (6th August 2013) - Ye, Jiandong; Lim, Sze Ter; Gu, Shulin; Tan, H. Hoe; Jagadish, Chennupati; Teo, Kie Leong; Chauveau, Jean‐Michel; Sallet, Vincent; Morhain, Christian; Feuillet, Guy
Abstract In this study, the origin and transport properties of high mobility carriers of two‐dimensional electron gas (2DEG) at ZnMgO/ZnO interface have been investigated. It is found that the observed experimental dependence of carrier sheet density of 2DEG on ZnMgO thickness and Mg composition exhibits an excellent agreement with the theoretical calculations based on the surface charge model. It indicates that the mobile electrons in 2DEG are originated from the donor‐like surface states. Moreover, the anomalous periodicity of Shubnikov‐de Haas oscillations has been observed and the partial spin polarization feature of 2DEG has also been demonstrated, which exhibits the promising development in oxide spintronics applications. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)